Association between diabetic retinopathy and hemoglobin level - Bahar, Adele (Babol University of Medical Sciences, 2013)
Background: Anemia may be considered to be an independent risk factor for the development of diabetic retinopathy (DR) in patients with renal failure. The purpose of this study was to investigate the association between blood hemoglobin level and retinopathy in diabetic patients with normal renal function tests. Methods: From 2009 to 2011, 1100 diabetic patients underwent retinal examination. Among them, 159 subjects were diagnosed to have DR and were compared with 318 diabetic subjects with normal retinal examination as the control group. The level of hemoglobin (Hb), Hb A1C, serum iron, ferritin, and total iron binding capacity were compared between these two groups. Results: Among the 159 patients with DR, 112 (70.4%) had mild to moderate no proliferative retinopathy (NPDR) and 47 (29.6%) had advanced retinopathy (severe NPDR or proliferative). The mean hemoglobin level in case and control group was 12.15±1.50 and 12.73±1.38 g/dl, respectively (p<0.001). Anemia was seen in 45.9% and 26.1% in the case and the control groups, respectively (p<0.001). Ferritin <15ng/ml was seen in 7.4% and 6.1% of patients with and without DR, respectively (p=0.8). Conclusion: The results show that diabetic patients with retinopathy have lower level of hemoglobin and higher frequency of anemia. It is suggested that the level of hemoglobin should be evaluated periodically in diabetic patients.